Improving Employee Performance: The Role of Motivation and Work Discipline in a Companies House in Bandung - Pratama, Yuda; Suzanto, Boy; Mialasmaya, Siti; Tansar, Indri Ayu; Ningsih, Tri (Informatics Management, Engineering and Information System Journal, 2024)
This study assesses the impact of motivation and work discipline on employee performance, individually and collectively. It examines 40 employees and uses a questionnaire to acquire data. The study utilizes path analysis, demonstrating that the motivation variable (X1) exerts a direct influence of 27.2% and an indirect effect via its association with work discipline (X2) of 9.3%. The cumulative effect is 36.5%. The work discipline variable (X2) exerts a direct effect of 22.6% and an indirect effect via its association with motivation (X1) of 9.3%, culminating in a total effect of 31.9%. The coefficient of determination (R Square), represented as a percentage, reveals that the two independent variables—motivation (X1) and work discipline (X2)—account for 68.4% (0.684), whereas the residual value is Ɛ = 31.6% (0.316). In conclusion, many recommendations derived from the research findings advocate for enhancing motivation and work discipline to elevate employee performance. In conclusion, many recommendations derived from the research findings advocate for enhancing motivation and work discipline to elevate employee performance. This research underscores the necessity of creating specialized training programs that enhance motivation and strengthen employee work discipline. Organizations should build incentive systems and recognition programs that honor employee accomplishments, establishing explicit performance criteria and accountability metrics. By concentrating on these domains, organizations may cultivate a more engaged and productive staff, enhancing overall performance and market competitiveness.